(3EQTGOGJ aj NOeI hQYGjI GdfHGJGJ GdHSJGfjI (B/s - (3GdYdGa, GjGO gGfj GSeGYjds ((3YeGf, GdCQOf (B:s (3OGQ OLdI fGTQhf hehRYhf,s, 2017)
(3jJfGhd cJGH (B((3EQTGOGJ aj NOeI hQYGjI GdfHGJGJ GdHSJGfjI(B) (3hGdPj bGe HJCdjag (B((3EjGO gGfj ESeGYjd GdYdGa(B) (3aj MhGdj (B(224) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3adGMI GdHSGJjf(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3JQHjI CTLGQ GdJjf HWQjbI GdhSW GdeaJhM (B((3GdJQHjI GdcGSjI(B)(3, JYQa Ydi cjajI JfSjb GdfHGJGJ OGNd efRdc, JfejI TJdGJ GdMHI GdNVQGA HGSJNOGe eSJNdUGJ GdCYTGH GdHMQjI, cja jDKQ GdVhA aj feh GdeMGUjd GdHSJGfjI, CSHGH bdI YbO GdKeGQ hGdMGUd aj CTLGQ GdaGcgI, GdTJd hEfJGL TJdGJ GdNVQGhGJ(B... (3EdN(B.s
(3ShaJ(B.s
Keywords: (3adGMI GdHSGJjfs; (3ZQS GdfHGJGJs; (3GdRQGYI s -- (3GbJUGOjGJs